Effect of Green Mussel Raft Culture to Total Organic Matter (TOM) and Flux of Dissolved Inorganic Nitrogen (DIN) in Sriracha Bay, Chon Buri Province - Peng-ngeiw, Pranitda; Jaritkhuan, Somtawin; Tunkijjanukij, Suriyan (Burapha Science Journal, 2026)
Total organic matter (TOM) in sediment and flux of dissolved inorganic nitrogen (DIN) at the water-sediment interface in Sriracha Bay, Chon Buri Province, were investigated in August 2014, December 2014 and April 2015. Samples of water and sediment were taken from three stations: The first station was identified as an area where there was no green mussel raft culture activity, the second station was in an area where green mussel raft culture activities were just performed for 1-2 years. The third station was identified as an area where green mussel raft culture has been performed for over 10 years. Total organic matter (TOM) showed high values in the area which has been used for mussel culture for more than 10 years (5.71±2.44 %). The prolonged green mussel raft culture has a major effect on the sediment texture as well as on the components of the sediment. The values of DIN fluxes were higher in the area of the prolonged culture for over 10 years than the one of 1-2 years. The lowest DIN fluxes were found in the area with no mussel raft culture activity. Flux of nitrite, nitrate and ammonia in the area where green mussel raft culture has been performed for over 10 years were 7.97, 32.60 and 39.92 µmol.m-2.h-1, respectively. Flux of DIN at the water-sediment interface moving from the sediment to the water, indicated that the sediment in the green mussel culture area acted as a source of DIN.